Rencana Bisnis pada Pelayanan Pendidikan Nonformal - Hadi, Rizal; Wahidmurni; Zuhro, Ni'matuz; Yanah, Nur (Universitas Airlangga, 2025)
Business plan design skills are essential competency for entrepreneurs, as a well-crafted business plan helps stakeholders easily understand and trust the proposed document. This study aims to describe business planning analysis from four key perspectives: (1) marketing, (2) operations, (3) human resources, and (4) finance, and focusing on the case of Gama Private Center, a non-formal educational institution. This study used qualitative case study approach. The findings reveal that Gama Private Center employs a structured business plan that includes: (1) a marketing strategy informed by market research and a marketing mix; (2) human resource planning encompassing recruitment processes, training, and compensation schemes; (3) operational strategies focusing on customer proximity, engaging learning methods, and user-friendly Standard Operating Procedures (SOPs); and (4) financial planning, including initial capital calculation, funding identification, cash flow forecasting, and financial feasibility analysis. The study contributes theoretically by advancing the understanding of business planning concepts in non-formal education, emphasizing market analysis, consumer segmentation, and operational strategies for success. Practically, it provides actionable insights for non-formal education entrepreneurs, including consumer-centered marketing strategies, human resource development, and structured business planning to enhance competitiveness and sustainability. Future research is recommended to explore the scalability of these strategies across diverse educational contexts